Dynamic of soil labile carbon in forest systems of Eucalyptus grandis Hill ex Maiden in the Argentinean Mesopotamia - Romaniuk, Romina I; Venece, Matias; Cosentino, Vanina R N; Alvarez, Carina R; Ciarlo, Esteban A; Korsakov, Helena Rimski; Steinbach, Haydée S; Lupi, Ana M (Bosque (Valdivia), 2021)
The amount and quality of carbon from forest litter present in the soil will depend on several factors, including species composition, management practices, plantation age, climatic conditions and soil texture, among several other factors. The aims of this research were to: i) quantify the labile organic carbon content in soils with Eucalyptus grandis plantations of the Mesopotamian region in Argentina and evaluate its relationship with the amount and type of litter; and ii) identify management, edaphic and environmental factors that may influence its variation. The study was performed on young and middle age plantations having soils with sandy and clayey texture located in the Gualeguaychú district, Entre Ríos, Argentina. To quantify the labile carbon in the soil, the soluble organic carbon was extracted with a 0.5M potassium sulfate solution. Soluble organic carbon concentration did not differ according to the age of the stands, with average values of 45.6 mg kg-1 in clay soils, and of 32.8 mg kg-1 in sandy soils, showing a positive association with clay content. The highest soluble organic carbon values were recorded during the summer months, and were positively related to the increases in the water-saturated pore space and the soil biological activity. We also verified a linear and positive relationship between the amount of initial fine litter and the increase of soluble organic carbon in the soil (R2 = 0.41). The reported results provide explicit ranges of variability for total organic carbon, soluble organic carbon and carbon fluxes at local level; thereby contributing to further characterize carbon modeling in forest systems.